Cardiovascular Co-morbidity in COVID-19 Pandemic - Tamrakar, Rikesh; Amgain, Kapil; Sajed, Ahmad Naeem (Europasian Journal of Medical Sciences, 2020)
At present, we are in the middle of a global pandemic due to COVID 19 disease caused by SARS-CoV-2 viral infection. It has now spread virtually to every corner of the globe. Medical professionals are faced with the challenge of managing diverse clinical manifestations and multisystem involvement of this infection. Although the respiratory system is mainly involved in COVID-19 disease, there have been diverse manifestations within the cardiovascular (CV) system that pose unique therapeutic challenges. Clinically, a patient may have features of myocarditis, heart failure, acute myocardial infarction, arrhythmia, and vascular thrombosis. Of these manifestations, the most common mechanism implicated is direct myocardial injury, whereas systemic inflammation, oxygen supply-demand mismatch, plaque rupture have also been suggested. Furthermore, currently available data suggest cardiovascular-related manifestations lead to increased morbidity and mortality. Also, patients with underlying cardiac conditions are more prone to severe disease and death. Although there are limited treatment options available for COVID-19 currently, it is imperative that the potential cardiovascular implications of these therapies are to be considered in these patients. There is a need to review currently available information regarding the implication of cardiovascular co-morbidity in COVID-19 disease so that we have an up-to-date and better understanding of this global problem. This review highlights the manifestations, pathophysiological mechanisms for cardiovascular manifestations of COVID-19 and addresses specific concerns of cardiac patients regarding medications and further management.